New occurrences of Palaeopascichnus from the Stáhpogieddi Formation, Arctic Norway, and their bearing on the age of the Varanger Ice Age. - Jensen, Sören; Högström, Anette; Høyberget, Magne; Meinhold, Guido; McIlroy, Duncan; Ebbestad, Jan Ove R.; Taylor, Wendy L.; Agic, Heda; Palacios, Teodoro (Canadian Journal of Earth Sciences, 2018)
Accepted manuscript version. Published version available at https://doi.org/10.1139/cjes-2018-0035 . Copyright NRC Research Press. We report on new occurrences of the late Ediacaran problematicum Palaeopascichnus (Protista?) from the Stáhpogieddi Formation, Arctic Norway. The stratigraphically lowest occurrences are in beds transitional between the Lillevannet and Indreelva members: the highest in the second cycle of the Manndrapselva Member, stratigraphically close to the lowest occurrences of Cambrian-type trace fossils. This establishes a long stratigraphical range of Palaeopascichnus on the Digermulen Peninsula, as has been previously documented from Newfoundland, South Australia, and elsewhere in Baltica. The age range of Palaeopascichnus in Avalonia and Baltica is from ∼565 to 541 Ma. Since the transition from the Mortensnes Formation to the Stáhpogieddi Formation is without a major break in sedimentation, this supports the inference that the underlying glacigenic Mortensnes Formation is ca. 580 Ma, and therefore Gaskiers-equivalent, or younger.